2020
DOI: 10.7307/ptt.v32i1.3203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effectiveness of Speed Reduction Markings on Driving Speed in Highway Tunnel Entrance and Exit Areas

Abstract: Tunnels are critical areas for highway safety because the severity of crashes in tunnels tends to be more serious. Controlling vehicle speed is regarded as a feasible measure to reduce the accident rate in the tunnel entrance and exit areas. This paper aims to evaluate the effectiveness of three types of speed reduction markings (SRMs) in tunnel entrance and exit zones by conducting a driving simulation experiment. For this study, 25 drivers completed the driving tasks in the day and night scenarios. The vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…At present, scholars have carried out a lot of research on the entrance and exit sections of tunnels, which can be mainly divided into the following categories: pavement temperature fields [1][2][3], linear setting [4][5][6][7], brightness design [8][9][10][11][12][13], and operation safety [14][15][16][17][18]. Despite these studies, there are few ones on the mechanical response characteristics of the pavement structures in these sections.…”
Section: Introductionmentioning
confidence: 99%
“…At present, scholars have carried out a lot of research on the entrance and exit sections of tunnels, which can be mainly divided into the following categories: pavement temperature fields [1][2][3], linear setting [4][5][6][7], brightness design [8][9][10][11][12][13], and operation safety [14][15][16][17][18]. Despite these studies, there are few ones on the mechanical response characteristics of the pavement structures in these sections.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the particularity of traffic environments, tunnels have become the main spatial distribution points of accident-prone traffic sections, which seriously affects highway safety [4]. Compared with general roads, the death rate of highway accidents is twice higher [5], especially with the increasing frequency of traffic accidents in highway tunnels, which has affected traffic safety dramatically and caused significant social and economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…When the ambient luminance and luminance uniformity meet certain conditions, drivers will be able to adapt to the environment and identify objects more easily, thus ensuring driver safety. Studies have also found that when drivers approach a tunnel, at the entrance zone they experience a large difference in luminance, which causes a corresponding change in the driver's psychology, thus affecting their true perception of the tunnel light environment information and even leading to traffic accidents (23)(24)(25)(26). Therefore, it is necessary to represent the psychological reaction of drivers in the complex light conditions at the entrance zones of tunnels by multiple psychological indicators.…”
mentioning
confidence: 99%